A CONCEPTUAL CLEANSOLUTION BUSINESS MODEL: EMPOWERING LOW-INCOME B40 COMMUNITIES AS ENTREPRENEURS THROUGH HOUSEKEEPING AND SERTU CLEANING SERVICES - AMER SHARIFFUDIN, NURRDINAN SERENA; WAN AHMAD SAYUTI, WAN MAIZATUL AKMAL; MHD KAMIL, NUR FAIZAH; YASLAM BABATAT, ZAKARYA AHMED; AHMAD DAHLAN, ABDUL RAHMAN (Journal of Information Systems and Digital Technologies, 2023)
This paper discusses a conceptual business model of housekeeping service, called CleanSolution that aims to provide property care and cleaning management services through the use of a digital platform for business operations. The platform is intended to improve connectedness between housekeeping and sertu cleaning service companies and their workers, aligned to the first, third and eighth Sustainable Development Goals (SDGs) of no poverty (SDG1), good health and well-being (SDG3) as well as decent work, and economic development (SDG8). The critical challenge for CleanSolution is to focus on creating work opportunities for B40s and nurturing B40 cleaning entrepreneurs through sertu cleaning services that will benefit potential customers in terms of creating decent work & economic growth (SDG8) for individuals and the country. On top of that, the business provides a sustainable cleaning service including Sertu cleaning which is a Shariah compliance cleaning method for Muslim customers, through a trusted online platform as a medium of communication between customers, workers and the sertu cleaning service companies. CleanSolution is designed, tested, and established as a multi-sided platform business, after conducting surveys in understanding the problems faced by the various customer segments (CS) - customers, workers and the housekeeping & sertu cleaning service companies. Design thinking methodology has been adapted in this paper including empathising, defining, ideating, prototyping, and testing. The paper outlines the creation of both a Business Model Canvas (BMC) and a Value Proposition Canvas (VPC) to guide the development and implementation of the digital platform.